ANALISIS PERBANDINGAN FITUR SISTEM REKOMENDASI PADA PLATFORM STREAMING DIGITAL: STUDI DESKRIPTIF NETFLIX, SPOTIFY, DAN YOUTUBE - Michel Michel; Stevany Angel; Noviana Engelica; Dorie Kesuma P. (CV. Denasya Smart Publisher, 2026)
Digital streaming platforms such as Netflix, Spotify, and YouTube have become an inseparable part of Indonesian society's digital life. Each platform features a content recommendation system designed to enhance user engagement and satisfaction. This study aims to analyze descriptively and qualitatively and compare the recommendation system features implemented by these three platforms. Data were collected through direct observation, literature review, and official documentation analysis. Results show that the three platforms adopt different personalization approaches: Netflix emphasizes visual personalization, Spotify excels in activity context understanding, while YouTube relies on real-time engagement signals. This study provides a comprehensive overview of each platform's characteristics that can serve as a reference for developing local recommendation systems in Indonesia.